2015
DOI: 10.1155/2015/670327
|View full text |Cite
|
Sign up to set email alerts
|

Actual Anatomical and Dosimetric Changes of Parotid Glands in Nasopharyngeal Carcinoma Patients during Intensity Modulated Radiation Therapy

Abstract: The goal of this study was to evaluate the actual anatomical and dosimetric changes of parotid glands in nasopharyngeal carcinoma patients during intensity modulated radiation therapy. With helical tomotherapy, its planning system, and adaptive software, weekly anatomical and dosimetric changes of parotid glands in 35 NPC patients were evaluated. Interweekly parotid volume varied significantly (P < 0.03). The rate of volume change reached the highest level at the 16th fraction. The average V 1 increased by 32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…As shown by published studies, parotid volume decreases when the gland migrates into the high-dose volume during radiation therapy for NPC patients, leading to a higher actual parotid dose than was intended in the initial planning [8,14]. In our study we observed that the actual parotid mean increased, as well as 1 and 50 , after a single fraction.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…As shown by published studies, parotid volume decreases when the gland migrates into the high-dose volume during radiation therapy for NPC patients, leading to a higher actual parotid dose than was intended in the initial planning [8,14]. In our study we observed that the actual parotid mean increased, as well as 1 and 50 , after a single fraction.…”
Section: Discussionsupporting
confidence: 70%
“…Someone recommended replanning when it became obvious that a tumor had shrunk, weight loss had occurred, or skin separation had reduced [7,11,12,[21][22][23], while others believe that replanning should be performed when a specific fraction has been reached [26][27][28]. Our precious study found that parotid volume variation presented a linear pattern throughout IMRT of NPC realized by HT technique, and the rate of volume variation reached its peak at the 16th fraction and then decreased gradually, suggesting that replanning is appropriate in the fourth week [14]. In this study, we raised the specific criteria coupled with timing of replanning for parotid protection-based ART in NPC.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations